2021
DOI: 10.1093/rheumatology/keab904
|View full text |Cite|
|
Sign up to set email alerts
|

Parvovirus B19 induces cellular senescence in human dermal fibroblasts: putative role in systemic sclerosis–associated fibrosis

Abstract: Objective Emerging evidence demonstrates that excessive accumulation of senescent cells is associated with some chronic diseases and suggests a pathogenic role of cellular senescence in fibrotic processes, such as that occurring in aging or in systemic sclerosis (SSc). Recently, we demonstrated that parvovirus B19 (B19V) activates normal human dermal fibroblasts and induces expression of different profibrotic/proinflammatory genes. This observation prompted us to investigate whether it is als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 50 publications
1
10
0
Order By: Relevance
“…Recent studies supported the role of a genetic predisposition and both endogenous and/or exogenous environmental triggers may be promoter for epigenetic mechanisms in genetically predisposed population [1][2][3][4][5][6][7][8][9][10][68][69][70][71][72][73][74][75]. Interestingly, a recent study supported the role of infectious triggers in SSc pathogenesis; in particular, the authors reported a possible role of Parvovirus B19 in this disease [15].…”
Section: Systemic Sclerosis Pathogenesismentioning
confidence: 82%
See 4 more Smart Citations
“…Recent studies supported the role of a genetic predisposition and both endogenous and/or exogenous environmental triggers may be promoter for epigenetic mechanisms in genetically predisposed population [1][2][3][4][5][6][7][8][9][10][68][69][70][71][72][73][74][75]. Interestingly, a recent study supported the role of infectious triggers in SSc pathogenesis; in particular, the authors reported a possible role of Parvovirus B19 in this disease [15].…”
Section: Systemic Sclerosis Pathogenesismentioning
confidence: 82%
“…The SSc vascular damage is characterized by the presence of a characteristic processes with a vasomotor instability with an imbalance of vasoactive factors: overproduction of vasoconstrictors (ET-1) and underproduction of vasodilators (NO and prostacyclin) [6][7][8][9][10][11][12][13][22][23][24][25][106][107][108][109]. The free radical nitric oxide (NO) is a potent vasodilator and is synthesized from L-arginine by NO synthase (NOS) [10][11][12][13][14][15][16][17][18][19][22][23][24][25][40][41][42][43][44][45][46][47][48][106][107][108][109][110][111][112][113]. Endothelial isoforms of NOS (eNOS or NOS 3) has been identified with a constitutive expression, other isoforms are shown...…”
Section: The Role Of Endothelial Injury In Systemic Sclerosis Pathoge...mentioning
confidence: 99%
See 3 more Smart Citations